2022
DOI: 10.3390/biology11040550
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Oxidative Stress as Common Mechanisms of Pulmonary, Autonomic and Musculoskeletal Dysfunction after Spinal Cord Injury

Abstract: One of the etiopathogenic factors frequently associated with generalized organ damage after spinal cord injury corresponds to the imbalance of the redox state and inflammation, particularly of the respiratory, autonomic and musculoskeletal systems. Our goal in this review was to gain a better understanding of this phenomenon by reviewing both animal and human studies. At the respiratory level, the presence of tissue damage is notable in situations that require increased ventilation due to lower thoracic disten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 120 publications
(163 reference statements)
0
7
0
Order By: Relevance
“…After SCI, the local tissue structures are disrupted, leading to antigen exposure at the site. [50] MBP, a crucial constituent of the myelin sheath, is frequently exposed after SCI and triggers immune cell activity. [51] A91-DsEVs stimulated the conversion of CD4 + T cells into antigen-specific Th2 and Treg cells, enabling their recruitment to injury sites.…”
Section: Discussionmentioning
confidence: 99%
“…After SCI, the local tissue structures are disrupted, leading to antigen exposure at the site. [50] MBP, a crucial constituent of the myelin sheath, is frequently exposed after SCI and triggers immune cell activity. [51] A91-DsEVs stimulated the conversion of CD4 + T cells into antigen-specific Th2 and Treg cells, enabling their recruitment to injury sites.…”
Section: Discussionmentioning
confidence: 99%
“…This necessitates the exploration of new predictive factors. In particular, a reduction in sympathetic nervous system stimulation neurons can cause disorders in catecholamine secretion of the adrenal medulla during exercise, leading to decreased levels of blood catecholamines, heart rate, cardiac output, and ventilation, ultimately limiting cardiopulmonary function [ 28 , 29 ]. Therefore, an equation that includes pulmonary function can be considered as a factor for predicting VO 2 peak in individuals with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms explain this behavior; it has been shown that these patients’ airways have a decreased radius, partly due to lower respiratory muscle strength and lower thoracic excursion, as well as the difficulty in mobilizing secretions that affect the airway radius and, ultimately, in many cases, a compromise of the sympathetic nerves that correspond to the main bronchodilator factor through the adrenergic system of the airway’s smooth muscle [ 25 ]. In addition, the increased parasympathetic tone described in some patients further favors bronchial reactivity by increasing the work of breathing [ 26 , 27 ]. Ultimately, the poor pulmonary function described in this group decreases access to the large physiological pulmonary reserve, leaving patients unable to adequately respond to stressful situations.…”
Section: Pulmonary Effects Of Spinal Cord Injurymentioning
confidence: 99%